Perception on SI + SA as a theme in a work of art entitled "free memories" / Noor Enfendi Desa ... [et al.] - Desa, Noor Enfendi; Muhamad, Noor A'yunni; Syed Abu Bakar, Syed Alwi; Tahir, Azian (Universiti Teknologi MARA, Perak, 2021)
The effects from thinking will result in the production of perception. This perception exists in both positive and negative situations. It focuses on the cognitive that explains how human brain responds to the perceptions received from their respective methods of understanding. The exhibition of "Kami 8: SI + SA" has managed to exhibit creative artwork produced by academic staffs from the Faculty of Art and Design UiTM Perak, with the appreciation of the theme "SI + SA" will change the way of delivery or meaning, according to the circumstances and methods of individual personal perception. The research design is based on J.J. Winklemann in producing art works. Data collection consisting of sampling and equipment based on ideal imagery observation methods. Also, samples and equipment were analyzed based on the production of the proposed artwork based on the studio-based research. The artwork "free memories" is produced based on perception and understanding by the author translating in visual form.